Mycorrhiza in Eucalypts in India - Bakshi, B. K. (Indian Forester, 1966)
Ectotrophic mycorrhiza has been recorded in 14 species of Eucalyptus, belonging to different sections, planted as exotics in India. The fungal symbiont of the mycorrhiza is identified as Scleroderma verrucosum (Bull.) Pers. Mycorrhiza was not introduced prior to plantings. The eucalypts were able to develop mycorrhiza with the fungal symbiont that may have been already present in the site. This is significant since in the success of exotics, introduction of mycorrhiza is necessary but may not be always so, if the fungal symbiont is already present in the r ew home as observed in the present investigation.